The Contribution of Fiscal Policies to the Industry Sector - Yunanto, Muhamad; Medyawati, Henny (Global Journal of Social Sciences Studies, 2020)
Fiscal policy is an adjustment in government revenue and expenditure as stipulated in the state revenue and expenditure budget in order to achieve better economic stability and pace of development. Several studies have shown that there is a relationship between fiscal policy and industrial sector output. The main objective of this study is to measure and analyze the contribution of fiscal policy on the industrial sector. The variables used in this research are industrial sector GDP, BI interest rate, government expenditure and tax revenue. The appropriate model for time series data that is not stationary is the Vector Error Correction Model (VECM). The data used are quarterly data from 1999 to 2019. The empirical results show that the industrial sector has a positive response to the shock of tax revenue variables and the consumer price index. On the other hand, the industrial sector responded negatively to shocks from government spending and the BI interest rate. The results of the variance decomposition analysis show that government spending provides the largest contribution to the industrial sector compared to other variables in this study.